Generalization of a fast, predictive model for tokamak scenario design in ASTRA and comparison to a RAPTOR model - Raphael Schramm; Alexander Bock; Emiliano Fable; Jörg Stober; Simon van Mulders; Marc Maraschek; Rainer Fischer; Andreas Burckhart; Philip Schneider; Olivier Sauter; Hartmut Zohm; the ASDEX Upgrade Team; et al. (Nuclear Fusion)
Early heating tokamak plasmas during the current ramp-up is a common approach to efficiently access advanced tokamak (AT) configurations. We have previously presented an analytical predictive model to aid in the AT scenario design, optimized for a single scenario (Schramm et al 2024 Nucl. Fusion 64 036013). We now show that this approach can be generalized to other scenarios and even other devices. To this end, we present results from an AUG scenario with higher current ( $q_{95}\sim 4$ ) and central counter-ECCD for elevated q -profiles, as well as from JET flux pumping experiments. For both cases, good agreement with the experiment could be shown with only minor changes to the model’s transport parameters. Comparisons with an alternative approach (Mulders et al 2024 Nucl. Fusion 64 026021) based on the RAPTOR code have also been carried out with good agreement.